(untitled) (Economics and region, 2023)
The article examines the concept and outlines the components of the "information space of controlling information" category. Given the study of the information space of a joint venture as a system representing a single whole with a set of interconnected and interacting components - information objects, but on a smaller scale within the external and internal environment, the author develops a mechanism for the formation of information security with the allocation of information flows by directions (entry into the system, processing in the system, exit from the system), which allows to schematically depict the impact of information from the external information space on the joint venture’s activities, information processing processes in the management system, management decision-making based on the processed information, as well as the output of high-quality and reliable information to meet the information needs of external users. When organising information security, it should be borne in mind that the vast majority of threats are generated by its employees, regardless of whether it is information in the form of employee knowledge or information contained in documents. The paper focuses on office threats to information of business entities, namely, threats to information contained in documents and information possessed and used by office workers in the course of their work. Since the set of actions of the personnel of a certain entity, aimed at ensuring the management of its activities, is appropriately organised in space and time, work with information of an enterprise, and work in the management link, determines the particular importance of such activities. A large amount of financial information can lead to the inability to process all the information, reduce the likelihood of assessing the most appropriate and reliable information, and make erroneous management decisions. The emergence and intensification of threats in the information environment significantly increases the importance and role of information security for the national security of Ukraine. As a result of the research of the selected topic, reasonable conclusions have been drawn which make it possible to define the concept of "financial controlling information" as a set of diverse data produced by individual structural units of business entities, public authorities, other institutions and organisations and used in the process of preparing reports for managers of various levels in order to make the right management decisions.